Prevalence, Predictors, and Implications for Appropriate Use of Active Surveillance Management Among Black Men Diagnosed With Low-risk Prostate Cancer. (June 2019) - Taku, Nicolette; Narayan, Vivek; Wang, Xingmei; Vapiwala, Neha
Abstract : Background: Consensus guidelines recommend that active surveillance (AS) be considered in the management of men with low-risk prostate cancer (LRPC). The objective was to evaluate the prevalence and predictors of an AS approach in black men (BM) diagnosed with LRPC after inclusion of AS in LRPC consensus guidelines. Materials and Methods: BM and white men (WM) diagnosed with LRPC (prostate-specific antigen ⩽10 ng/mL, Gleason score [GS] ⩽6, clinical stage T1-T2a) between 2010 and 2013 were identified from the National Cancer Database. Logistic regression models were used to assess the likelihood of AS over time and to examine associations between sociodemographic characteristics (SDCs) and the receipt of AS. A subanalysis was performed to assess the likelihood of GS upgrading on prostatectomy specimens for cases that received definitive treatment with radical prostatectomy. Results: Overall, 9% of BM (N=15, 242) with LRPC were managed with AS. The likelihood of BM undergoing AS increased from 2010 and for all subsequent years of the study period ( P <0.001). Uninsured BM were twice as likely as those with private insurance to undergo AS (odds ratio [OR]=1.97; 95% confidence interval [CI], 1.51-2.58; P <0.001). BM were less likely than WM (N=86, 655) to receive AS (OR=0.82; 95% CI, 0.77-0.87; P <0.001). However, on multivariate analysis adjusted for SDCs, there was no significant difference in AS utilization between the 2 race groups. Nearly half of BM (47.5%) treated with radical prostatectomy had a postprostatectomy GS≥7, and BM were 17% more likely to experience postprostatectomy upgrading to GS≥7 when compared with WM (OR=1.17; 95% CI, 1.08-1.26; P <0.001). Conclusions: The utilization of AS for BM with LRPC seems to be increasing, is influenced by SDCs, and may not differ from AS utilization among WM. Careful consideration of prostate biopsy technique and sampling as well as SDCs at time of treatment planning may be necessary to ensure adequate evaluation of prostatic disease and appropriate disease management for BM with LRPC.